Kredit Macet Pada LPBBTI Sebagai Wujud Perlindungan Hukum - Kusumo, Suryo; Yudhantaka, Lintang (Legal Spirit, 2025)
The development of technology that penetrates the world of economics has a significant impact on the financial sector in Indonesia. With the presence of Financial Technology financial institutions with the P2P Lending system, it is considered to be able to help the community's economy. However, on the other hand, it has a dark impact on the community so that it is prone to being tied to problems related to needs and the economy such as bad credit where someone experiences arrears in credit payments. Of course, this results in losses for the related financial institutions. This study aims to determine the legal position of the organizers of Information Technology-Based Joint Funding Services (LPBBTI) who experience bad credit and to understand the form of legal protection for the organizers of Information Technology-Based Joint Funding Services (LPBBTI) who experience bad credit. This study uses a normative legal research method. Data collection was carried out by means of literature and document studies. Data analysis was carried out using analytical descriptive methods and using a qualitative approach. The results of the study indicate that bad credit that can have legal consequences must be accepted by the recipient of funds because in this case it is very detrimental to the LPBBTI financial institution so that there needs to be an effort to protect the Organizer or Funder to avoid bankruptcy and revocation of the License by the Financial Services Authority.